Characterization Of ADC - Hasan, Muhamad Hasriq (Universiti Sains Malaysia, 2006)
This report consists of functional description, design of test circuit board, built up the PCB test circuit, also the measurement and characterization for ADC0804LCN analog to digital converter IC chip. This project is mainly to characterize the analog to digital converter IC. IC ADC0804LCN 8-bit national semiconductor is used as specimen IC to define several characteristics. To measure the characteristics of the IC, firstly have to design and built a test circuit board to make the IC operate. After that, implement several methods to characterize the IC. Linearity, clocking frequency, time conversion and relation between input voltage (Vin) and voltage reference over two (Vref/2) are the characteristics that measured in this project. This type of experiment that had been conduct can be used to measure characteristic of the IC such as linearity, clock frequency, time conversion and relation between input voltage and voltage reference over two.